Omnibus Law Policy in Encouraging Investment: Between Deregulation and Potential Legal Loopholes - Polontoh, Herry M (Ipso Jure, 2025)
The omnibus law policy  in Law Number 11 of 2020 concerning Job Creation was presented as a response to the complexity and fragmentation of national regulations that have long been the main obstacles to investment growth. Overlapping regulations between sectors, central-regional disharmony, and bureaucratic licensing procedures are considered no longer relevant to the demands of legal effectiveness and usefulness in the context of economic development. Using  a normative juridical approach, this study examines the formal and material validity of omnibus law within the framework of the Indonesian legal system, and examines its implications for the principles  of rule of law, social justice, and constitutional protection. The analysis was carried out through legislative, conceptual, and case approaches, especially the Constitutional Court Decision No. 91/PUU-XVIII/2020 which assesses procedural defects in the Job Creation legislation process. The results of the study show that although the omnibus law offers regulatory efficiency and ease of doing business, this approach leaves serious problems in the form of legal loopholes, multiple interpretations of norms, and potential violations of the principle of prudence in law formation. Therefore, the reformulation of deregulation policies based on the principles of the rule of law, public participation, and ecological justice is an urgent need to ensure that deregulation is not only pro-investor, but also in line with constitutional values and the sustainability of national development..